Does silica–nylon mesh improves the biomechanical response of custom-made mouthguards? - Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; de Carvalho, Paula Carolina Komori [UNESP]; Gonçalves, Pedro Henrique Pereira de Queiroz; Borges, Alexandre Luiz Souto [UNESP]; Paes-Junior, Tarcisio José de Arruda [UNESP] (Springer Nature, 2019)
Purpose: Mouthguards are used for injury prevention due to the high risk of dental and craniofacial injuries during sports activities. Therefore, the aim of this study was to evaluate the effect of silica–nylon mesh on the biomechanical performance of custom-made mouthguards using the finite element method. Methods: Two custom-made mouthguards were modeled according to the presence or not of silica–nylon mesh. A 500 N load was applied in the region of the upper central incisors for both models. A mesh convergence test of 10% was conducted in the computer-aided analysis software to reduce the error during the results processing. An ideal contact interface was used between all contacts, simulating a situation in which the athlete would not lose his mouthguard upon impact. Also, the contact between the reinforcement and the mouthguard was defined as frictionless after a microscopic investigation. Maximum principal stress parameter was analyzed for bone, mouthguard, teeth, and skull displacement. Stress peaks for mouthguards and teeth were analyzed using one-way ANOVA. Results: The results showed that the mesh presence neither influenced the skull displacement or the stress distribution in the bone, teeth or mouthguard. ANOVA showed no difference between the mesh presence or not, with 8.75 ± 2.00 MPa mean value for the mouthguard and 9.88 ± 2.75 MPa for the teeth. Conclusions: The presence of a silica–nylon mesh did not modify the biomechanical response in the bone, teeth or mouthguard. In addition, even with the mouthguards in position, some damage can occur after the trauma.
Keywords: Biomechanical response; Dental trauma; Finite element analysis; Mouthguard; Shock absorption